Early life stress and frailty in old age: the Helsinki birth cohort study - Haapanen, M. J. (BMC Geriatr, 2018)
BACKGROUND: Evidence suggests that early life stress (ELS) may extend its effect into adulthood and predispose an individual to adverse health outcomes. We investigated whether wartime parental separation, an indicator of severe ELS, would be associated with frailty in old age. METHODS: Of the 972 participants belonging to the present sub-study of the Helsinki Birth Cohort Study, 117 (12.0%) had been evacuated abroad unaccompanied by their parents in childhood during World War II. Frailty was assessed at a mean age of 71 years according to Fried’s criteria. RESULTS: Thirteen frail men (4 separated and 9 non-separated) and 20 frail women (2 separated and 18 non-separated) were identified. Compared to the non-separated men, men who had been separated had an increased relative risk ratio (RRR) of frailty (age-adjusted RRR 3.93, 95% CI 1.02, 15.11) that persisted after adjusting for several confounders. No associations were observed among women (RRR 0.62; 95% CI 0.13, 2.94). CONCLUSIONS: These preliminary results suggest that ELS might extend its effects not just into adulthood but also into old age, and secondly, that men may be more vulnerable to the long-term effects of ELS.